A Demi-decade of Mammal Research: A Rapid Assessment within the Heart of Borneo in Sabah - Mohd. Aminur Faiz Suis; Jabanus Miun; Lawrence Tingkoi; Alexander Yuk Loong Hastie; Arthur Chung Yaw Chyang; Reuben Nilus (Tropical Life Sciences Research, 2023)
Sabah contributes 4.2 million hectares to the total Heart of Borneo (HoB) areas. Some of the forest reserves in the HoB are newly gazetted as Totally Protected Forest. Hence, their mammal diversity has to be comprehensively documented. This study aims to record the presence of terrestrial mammal species, and assess the prevalence of poaching in selected forest reserves within the Sabah HoB area. A total of 15 forest reserves were surveyed within a 5-year timeframe which recorded 60 terrestrial mammal species, including 21 Bornean endemics. The variation in total enumerated mammal species in the study sites may be derived from unequal sampling efforts, geographical factors and anthropogenic influences. The intensity of poaching within the study sites is high. Though this study is a rapid assessment, it created baseline information for mammal diversity in some of the least studied forest reserves in Sabah, important for conservation of its terrestrial mammals.